2005
DOI: 10.1097/01.yco.0000165591.75681.ab
|View full text |Cite
|
Sign up to set email alerts
|

Innovative approaches to intervention for problem drinking

Abstract: There is strong support among potential users for alcohol interventions that employ telephone assistance, written correspondence, and the Internet. These new technologies offer the prospect of increasing the reach of interventions for problem drinking and being cost-effective alternatives or supplements to face-to-face health service delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…Preliminary evidence also suggests that self-help participation is associated with better outcomes when patients join groups that focus on their particular issues, such as dual diagnoses (Laudet et al, 2000) or adolescent issues (Finch, 2005; Kelly and Myers, 1997; Kelly, Myers, and Brown 2002; White and Finch, 2006). Other recently tested recovery support approaches include telephone-based self-monitoring (Simpson et al, 2005) and Internet-based groups (Klaw, Huebsch, and Humphreys, 2000; Kypri et al, 2005; Toll et al, 2003). A meta-analysis of 24 studies involving 3,739 participants with chronic health conditions (other than SUDs) suggests that Internet-based interventions that allow interactions between patients and staff have a significantly higher impact than sites providing information only (Murray et al, 2004).…”
Section: Emerging Approaches To Recovery Managementmentioning
confidence: 99%
“…Preliminary evidence also suggests that self-help participation is associated with better outcomes when patients join groups that focus on their particular issues, such as dual diagnoses (Laudet et al, 2000) or adolescent issues (Finch, 2005; Kelly and Myers, 1997; Kelly, Myers, and Brown 2002; White and Finch, 2006). Other recently tested recovery support approaches include telephone-based self-monitoring (Simpson et al, 2005) and Internet-based groups (Klaw, Huebsch, and Humphreys, 2000; Kypri et al, 2005; Toll et al, 2003). A meta-analysis of 24 studies involving 3,739 participants with chronic health conditions (other than SUDs) suggests that Internet-based interventions that allow interactions between patients and staff have a significantly higher impact than sites providing information only (Murray et al, 2004).…”
Section: Emerging Approaches To Recovery Managementmentioning
confidence: 99%
“…None of the alcohol‐related websites met all five guidelines 13 . In addition, many of the early publications on web‐based interventions were descriptive or reported on feasibility or on studies that were methodologically weak 14 , 15 . A recent review by Bewick and colleagues on web‐based interventions for alcohol consumption 16 found that only one intervention had used a randomised design that included a control of the highest standard according to their criteria 17 …”
mentioning
confidence: 99%
“…Many other current applications are employed in primary care settings, where the tremendous potential reach of computer-delivered approaches can be leveraged(e.g., Kypri et al, 2005). This is true of our own work, which has focused primarily on brief motivational interventions with low-income urban women who report use of drugs or alcohol in the post-partum period (Ondersma, et al, 2005; Ondersma, et al, 2007).…”
Section: Current Uses Of Intervention Technology In Substance Abusementioning
confidence: 99%
“…These advantages include greater ease of dissemination and replication, cost-effectiveness, anonymity, accessibility, and personalization (Copeland & Martin, 2004; Hester & Miller, 2006; Kypri, Sitharthan, Cunningham, Kavanagh, & Dean, 2005; Ondersma, Chase, Svikis, & Schuster, 2005). Interactive technology for promotion of behavior change has been supported by clinical trials of its use for alcohol abuse (Hester, Squires, & Delaney, 2005; Kypri, et al, 2004; Neighbors, Larimer, & Lewis, 2004), drug abuse (Gilbert, et al, 2008; Ondersma, Svikis, & Schuster, 2007), and sexual risk-taking (Kiene & Barta, 2006).…”
mentioning
confidence: 99%